A comparative analysis of mathematical methods for effective population size estimation - Molyte, Alma; Urnikyte, Alina; Kučinskas, Vaidutis (Lietuvos matematikos rinkinys, 2016)
In this paper two mathematical methods, McEvoy and Mezzavilla–Ghirotto, were investigated, they are devoted to determine the effective population size. Comparative analysis of two methods, for estimating effective population size, was performed.